UJI AKTIVITAS OBAT HERBAL GEL EKSTRAK DAUN GAHARU (Gyrinops versteegii (Gilg.) Domke) TERHADAP LUKA DIABETES PADA TIKUS PUTIH JANTAN (Rattus norvegicus) - Silvi Nurafni; Antonius Padua Ratu; Tia Marliana; Ega Rahmawati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
A study to test the activity of gel extract of gaharu (Gyrinops versteegii (Gilg.) Domke) leaf extract against diabetic wounds in male white rats (Rattus norvegicus). The research was conducted experimentally with the method of pre-test and post-test with group design. Gaharu leaf extract gel was formulated with concentrations of 4%, 6% and 8% and then tested for its activity on non-diabetic male white rats and diabetic male rats with alloxan induction. The negative control was given gel base and the positive control was given bioplacenton gel. The gel was administered once a day and the wound length was measured every day for 14 days. The results showed that all gel formulas of gaharu leaf extract had wound healing activity in non-diabetic rats and diabetic rats, the higher the concentration of the extract, the faster the wound healing and the greater the percentage reduction in wound length. The group of non-diabetic rats treated with gaharu extract gel with a concentration of 8% showed a wound length of 0,00 Â± 0,00 mm (wound healed) on day 6 with an average percentage reduction in wound length of 100,00 Â± 0,00 %. The results of statistical testing with Kruskal Wallis obtained p-value > 0.05 (p-value = 0.315) so it can be concluded that there was no significant difference between the treatment groups.